2013
DOI: 10.1891/0739-6686.31.277
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exercise on Cardiac and Metabolic Outcomes in People Living With HIV

Abstract: Poorly controlled HIV infection and antiretroviral therapy, especially the use of protease inhibitors, are among the causes that contribute to the development of cardiovascular disease in people living with HIV (PLWH). Poor lifestyle choices (smoking, lack of physical activity, poor diet) and individual factors such as high stress, physical or emotional trauma, depression, and so forth contribute to the overall risk of developing cardiovascular disease. The purpose of this review was to critically evaluate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
1
1
0
2
Order By: Relevance
“…Nowadays, HIV infection represents living with a chronic disease, which opens space for non-pharmacological interventions like physical exercise 21 . Physical exercise enables to maintain functionality and improves quality of life 22,23 , as our study has demonstrated. Thus, maintenance of physical and functional aptitude has become one of the priority objectives in the treatment of patients living with HIV/AIDS, mainly those with a diagnosis of pronounced loss of muscle mass 24 .…”
Section: Discussionsupporting
confidence: 63%
“…Nowadays, HIV infection represents living with a chronic disease, which opens space for non-pharmacological interventions like physical exercise 21 . Physical exercise enables to maintain functionality and improves quality of life 22,23 , as our study has demonstrated. Thus, maintenance of physical and functional aptitude has become one of the priority objectives in the treatment of patients living with HIV/AIDS, mainly those with a diagnosis of pronounced loss of muscle mass 24 .…”
Section: Discussionsupporting
confidence: 63%
“…After excluding studies pre-ART era, performed or published before or in the year 1996 [75], a significant change in the IG’s upper body strength (19.9 kg [95% CI: 12.3–27.5], p < 0.001) and lower body strength (15.1 kg [95% CI: 11.4–18.8], p < 0.001) was found, where the result for IG upper body strength was higher than that of the main meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Muito embora tenha possibilitado a reconstituição do sistema imunológico e o aumento da sobrevida das pessoas vivendo com HIV/AIDS, o uso prolongado da HAART, assim como a infecção pelo vírus HIV, causam alterações negativas e deletérias ao organismo desses sujeitos, tais como: complicações cardiorrespiratórias (diminuição do consumo de oxigênio), musculares (sarcopenia e diminuição da força muscular), psiquiátricas (depressão), alterações no perfi l bioquímico (redução nos níveis de HDL-c e aumentos de LDL-c e glicose), dentre outras. Essas alterações, quando analisadas separadamente, merecem atenção e, quando agrupadas, levam o organismo a desenvolver problemas cardiovasculares graves [5][6][7][8][9] . Dentre as alterações que pioram a qualidade de vida desses pacientes está a toxicidade mitocondrial de diversos tecidos, entre eles o hepático e o muscular, a qual leva à sua disfunção, fato que contribui substancialmente para a ocorrência de hiperlactacidemia de repouso [10][11] .…”
Section: Palavras-chave: Hiv/aids; Cinética De Lactato; Aptidão Físicunclassified
“…Dentre as alterações que pioram a qualidade de vida desses pacientes está a toxicidade mitocondrial de diversos tecidos, entre eles o hepático e o muscular, a qual leva à sua disfunção, fato que contribui substancialmente para a ocorrência de hiperlactacidemia de repouso [10][11] . Intervenções não-medicamentosas vêm sendo aplicadas para evitar/minimizar as consequências negativas advindas da associação entre a infecção do vírus HIV e o uso da HAART; dentre elas está a adesão ao programa de exercícios físicos regulares 2,5,[8][9][10]12 . Diversos estudos são encontrados na literatura mostrando os benefícios advindos do treinamento físico de força e aeróbio, tais como: aumento e manutenção do consumo máximo de oxigênio, adaptações neurais, aumento da massa e força muscular bem como redução do percentual de gordura, melhora nos perfi s lipídico e glicêmico, diminuição do risco coronariano, síntese de novas mitocôndrias e melhor vascularização (angiogênese), além da manutenção da carga viral e o aumento das células TCD4+ 5,9,[13][14] .…”
Section: Palavras-chave: Hiv/aids; Cinética De Lactato; Aptidão Físicunclassified